Ion Electron–Coupled Functionality in Materials and Devices Based on Conjugated Polymers. Issue 22 (8th January 2019) - Berggren, Magnus; Crispin, Xavier; Fabiano, Simone; Jonsson, Magnus P.; Simon, Daniel T.; Stavrinidou, Eleni; Tybrandt, Klas; Zozoulenko, Igor
Abstract: The coupling between charge accumulation in a conjugated polymer and the ionic charge compensation, provided from an electrolyte, defines the mode of operation in a vast array of different organic electrochemical devices. The most explored mixed organic ion–electron conductor, serving as the active electrode in these devices, is poly(3, 4‐ethyelenedioxythiophene) doped with polystyrelensulfonate (PEDOT:PSS). In this progress report, scientists of the Laboratory of Organic Electronics at Linköping University review some of the achievements derived over the last two decades in the field of organic electrochemical devices, in particular including PEDOT:PSS as the active material. The recently established understanding of the volumetric capacitance and the mixed ion–electron charge transport properties of PEDOT are described along with examples of various devices and phenomena utilizing this ion–electron coupling, such as the organic electrochemical transistor, ionic–electronic thermodiffusion, electrochromic devices, surface switches, and more. One of the pioneers in this exciting research field is Prof. Olle Inganäs and the authors of this progress report wish to celebrate and acknowledge all the fantastic achievements and inspiration accomplished by Prof. Inganäs all since 1981. Abstract : The coupling between ionic and electronic charge underlies an array of organic electrochemical devices. Prof. Olle Inganäs is a pioneer in this field, and this report celebrates his contributions by reviewing some of the achievements of the last two decades in organic electrochemical devices, in particular including PEDOT—the most explored organic mixed ion–electron conductor—as the active material.